Early Christianity in Macedonia : From Paul to the Late Sixth Century - Ogereau, Julien M., (Ancient Judaism and Early Christianity ;, 2023)
In this volume Julien M. Ogereau investigates the origins and development of Christianity in the Roman province of Macedonia in the first six centuries CE. Drawing from the oldest literary sources, Ogereau reconstructs the earliest history of the first Christian communities in the region and explores the legacy of the apostle Paul in the cities of Philippi, Thessalonica, and Beroea. Turning to the epigraphic and archaeological evidence, Ogereau then examines Christianity's dissemination throughout the province and its impact on Macedonian society in late antiquity, especially on its epigraphic habits and material culture.